The Similarity of Meaning in Lingual Forms of Lio Language: A Study of Meaning Relations in Isolating Languages - Bataona, Yosef; Sumbi, Agustinus Kembardi (ARRUS Journal of Social Sciences and Humanities, 2025)
Synonymy is a universal linguistic phenomenon found in every language. However, synonyms in each language have their own unique characteristics. This article focuses more intensively on the types of synonyms, their semantic features, and which type of synonymy is most dominant in Lio. Synonyms represent two or more linguistic units that differ phonologically and morphologically but have semantically similar meanings. Data were collected through observation, listening, and speaking, using listening and speaking techniques, as basic techniques, and recording and note-taking as advanced techniques. The results of the data analysis prove that absolute synonyms are rarely found in Lio, while the most dominant type of synonyms are partial synonyms with various interesting semantic features. Synonyms not only represent lexical variations but also have distinctive distinguishing features because they are highly determined by the situation, context, and socio-cultural background. The use of synonyms reflects the speaker's sensitivity to social situations, relationships between speakers, and the intensity of the emotions they wish to convey. The choice of appropriate synonymous words indicates the level of politeness, closeness, and even firmness of attitude in the Lio tradition.